Fibrinogen binding sites P336 and Y338 of clumping factor A are crucial for Staphylococcus aureus virulence. - FOSTER, TIMOTHY JAMES (My University, 2008)
We have earlier shown that clumping factor A (ClfA), a fibrinogen binding surface protein of Staphylococcus aureus, is an important virulence factor in septic arthritis. When two amino acids in the ClfA molecule, P336 and Y338, were changed to serine and alanine, respectively, the fibrinogen binding property was lost. ClfAP336Y338 mutants have been constructed in two virulent S. aureus strains Newman and LS-1. The aim of this study was to analyze if these two amino acids which are vital for the fibrinogen binding of ClfA are of importance for the ability of S. aureus to generate disease. Septic arthritis or sepsis were induced in mice by intravenous inoculation of bacteria. The clfAP336Y338 mutant induced significantly less arthritis than the wild type strain, both with respect to severity and frequency. The mutant infected mice developed also a much milder systemic inflammation, measured as lower mortality, weight loss, bacterial growth in kidneys and lower IL-6 levels. The data were verified with a second mutant where clfAP336 and Y338 were changed to alanine and serine respectively. When sepsis was induced by a larger bacterial inoculum, the clfAP336Y338 mutants induced significantly less septic death. Importantly, immunization with the recombinant A domain of ClfAP336SY338A mutant but not with recombinant ClfA, protected against septic death. Our data strongly suggest that the fibrinogen binding activity of ClfA is crucial for the ability of S. aureus to provoke disease manifestations, and that the vaccine potential of recombinant ClfA is improved by removing its ability to bind fibrinogen.
PUBLISHED
Keywords: Microbiology